Measuring The Nature of East Asia’s Automobile Production Networks - Shahrun Nizam Abdul Aziz; Normala Zulkifli; zainizam zakariya; Ramlee Ismail; Mohd Yahya Mohd Hussin; Fatimah Salwa Abdul Hadi; Azham Hussain (International Journal of Supply Chain Management, 2020)
The aim of this study is to explore the nature of East Asia’s automobile production networks by means of social-network methods. In this paper, we have also developed a domination degree index (DDI) and domination intensity index (DII) to measure the dominating power of each East Asian country in the automobile networks. The results suggested that the networks of East Asia’s automobile industry are expanding over time both in terms of the number of links in the network as well as the strength of those links. This result indicates that both export and import of automobile products in this region increase significantly over time. In addition, Japan has emerged as the main player, both in the case of auto parts and components (PC) and final automobiles. The Republic of Korea has also emerged as the second most important player in East Asia’s final automobile networks, while China has become the second most important player in East Asia’s auto PC networks. Even though Thailand is the third most important player in East Asia’s automobile networks in both auto PC and final automobiles, the analysis of this paper has suggested that there is a possibility for this country to overtake China and the Republic of Korea to become the second most important player in terms of both auto PC and final automobiles. The dramatic changes in the development of Thailand’s automobile industry as well as significant development in China’s auto PC have been made possible by the pivotal role played by Japan (on Thailand) and the Republic of Korea (on China) – all of which have stimulated the development of their subordinates’ auto industry in a so-called “win-win situation”